Dialektika Progresif; “One Dimensional Man”, Desublimasi Represif: Kritik Herbert Marcuse Atas Masyarakat Industri Modern - Sumarni, Lilik; Seran , Alexander (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2024)
Marcuse’s main idea is that technology and mass consumption have created a social order that makes people